Dexamethasone implant in the management of diabetic macular edema from clinician’s perspective - Urbančič M (Dove Medical Press, 2019)
Mojca Urbančič,1 Ivana Gardašević Topčić21Eye Hospital, University Medical Centre Ljubljana, Ljubljana, Slovenia; 2Department of Ophthalmology, General Hospital in Novo mesto, Ljubljana, SloveniaAbstract: The aim of this article is to provide an overview of characteristics and principles of use of dexamethasone implant in patients with diabetic macular edema (DME). The condensed information about patient selection, dosing, and postinjection management is provided to make the clinician’s decisions easier in real-life practice. DME is a common complication of diabetes and the leading cause of visual loss in the working-age population. Inflammation plays an important role in the pathogenesis of DME. The breakdown of the blood–retinal barrier involves the expression of inflammatory cytokines and growth factors, including vascular endothelial growth factor (VEGF). Steroids have proved to be effective in the treatment of DME by blocking the production of VEGF and other inflammatory cytokines, by inhibiting leukostasis, and by enhancing the barrier function of vascular endothelial cell tight junctions. Dexamethasone intravitreal implant has demonstrated efficacy in the treatment of DME resistant to anti-VEGF therapy and in vitrectomized eyes. Data from clinical trials suggest that dexamethasone implant can be considered as first-line treatment in pseudophakic eyes. Dexamethasone implant is also the first-line therapy in patients not suited for anti-VEGF therapy, pregnant women, and patients unable to return for frequent monitoring. It has been shown that the maximum effect of dexamethasone implant on visual gain and retinal thickness occurs approximately 2 months after injection. Various treatment regimens are used in real-life situations, and reported reinjection intervals were usually <6 months. The number of retreatments needed decreased over time. Treatment algorithms should be personalized. Postinjection management and follow-up should consider potential adverse events such as intraocular pressure elevation and cataract.Keywords: dexamethasone, diabetic macular edema, intravitreal implant, Ozurdex